APPROACHES TO ANTITHROMBOTIC THERAPY IN ELDERLY PATIENTS WITH ATRIAL FIBRILLATION - E. A. Ushkalova; S. K. Zyryanov; E. V. Dumchenko (Рациональная фармакотерапия в кардиологии)
Advanced age is the most important and independent risk factor for the development of atrial fibrillation (AF). The proportion of patients with AF at the age of 65-85 years reaches 70%, and average age of patients with AF is 75 years. Antithrombotic therapy of AF in the elderly is challenging for several reasons. On the one hand, elderly patients are at an increased risk of systemic embolism and stroke and fatal outcomes of stroke are higher in the elderly compared with these in the younger patients. On the other hand, elderlies are at an increased risk of bleeding. In addition, they have important comorbidities and are treated with drugs that can interact with antithrombotic agents. The article discusses tools used to assess risks of thromboembolic and hemorrhagic complications and general approaches to antithrombotic treatment of elderly patients.